Magnesium Sulfate Production ù First Value Added Salt From Saline Waters of the Murray Basin (Australia) - C Doblin; D Thomson; T Norgate; T Barto (The Australasian Institute of Mining and Metallurgy, 2004)
Collaboration between CSIRO Minerals and SunSalt Pty Ltd, a salt producing company located in rural Victoria, has resulted in a commercial process to recover magnesium sulfate (commonly called Epsom salt) from the saline waters of the Murray Basin. The feed for this process is bittern; the liquor remaining after halite (common salt) has been harvested from the saline water by evaporation.SunSalt produces salt and bitterns from three locations, namely Hattah (Victoria), Mourquong (NSW) and Wakool (NSW). The small size and considerable distances between these operations makes it uneconomic to build a stationary processing plant to extract value-added products, in particular Epsom salt, from the bitterns of the three operations. This fact led SunSalt to build a containerised mobile plant that could be moved to each site to process the bitterns at the end of the salt harvesting period.Epsom salt is extracted from the bittern by further evaporation, refrigeration and recrystallisation. In this process the bittern is diluted with five per cent volume of fresh water to minimise precipitation of residual halite in the bittern. Cooling the diluted bittern to between -5 and -10¦C precipitates up to 70 per cent of the magnesium sulfate, which is recovered as 85 to 96 per cent purity Epsom salt by filtration. This product is marketed as an industrial grade Epsom salt. Higher purity (up to 99.9 per cent) Epsom salt (USP or BP grade refined product) is made from the industrial grade product (raw Epsom salt) by recrystallisation.The containerised mobile plant was commissioned in December 2002. The raw Epsom salt generated in the mobile plant is refined to a higher purity Epsom salt in a separate plant located in Mildura. The Mildura plant was commissioned in December 2003.The CSIRO-SunSalt collaboration has demonstrated that the saline waters can be processed into a useful resource, and in addition could create jobs and a new skill base in regional Australia. The production of Epsom salt locally in Australia, which is worth currently about $A600 per tonne, removes the need to import over 3000 tpa from overseas with a net positive impact of $A2 million on the balance of trade.